Biodegradation of diclofenac and ibuprofen in Fluidized Bed Reactor applied to sanitary sewage treatment in acidogenic and denitrifying conditions. (October 2022) - de Melo Pirete, Luciana; Camargo, Franciele P.; Dornelles, Henrique S.; Granatto, Caroline F.; Sakamoto, Isabel K.; Grosseli, Guilherme M.; Fadini, Pedro S.; Silva, Edson Luiz; Varesche, Maria Bernadete Amâncio
Abstract: The diclofenac (DCF) and ibuprofen (IBU) removal were assessed in an enlarged scale denitrifying Fluidized Bed Reactor (FBR), fed with sanitary sewage plus ethanol (74–100 mg L −1 ) and nitrate (89–136 mg L −1 ). The experiment was sectioned into four phases. In Phase I the Hydraulic Retention Time (HRT) was set in 18 ± 3 h without DCF and IBU addition and the FBR shows a heterotrophic denitrifying behavior with 97 % nitrate removal. In Phase II the addition of pharmaceuticals did not change COD and nitrate removal. In Phase III the HRT was decreased to 12 ± 1 h which did not influence denitrification but decreased the efficiency of DCF (35 %) and IBU (40 %) removal. In Phases I, II and III the removal of organic matter was limited by the concentration of influent nitrate. The HRT was then increased in Phase IV to 18 ± 2 h and nitrate was not added to the feeding; which led to denitrification no longer being the preferential route and replaced by acidogenic metabolism, evidenced by the highest concentration and diversity of total volatile fatty acids (VFA), resulting in increased organic matter removal efficiency (56 %), DCF (53 %), IBU (56 %) and ethanol (99.7 %). In Phase IV, acidogenic bacteria were mainly responsible for DCF and IBU degradation by ω and β-oxidation. This study establishes that DCF and IBU biodegradation in FBR applied to sanitary sewage treatment in denitrifying condition is overcome by acidogenic metabolism in the absence of nitrate as an electron acceptor, favoring the pharmaceuticals degradation. Graphical abstract: Unlabelled Image Highlights: Fluidized Bed Reactor technology can remove diclofenac and ibuprofen in wastewater. Greatest diclofenac and ibuprofen removal (52.9–55.8 %) was found in acidogenic phase. Ethanol (88.9 mg L −1 ) was the main electron donor for heterotrophic denitrification. Acidovorax (9.38 %) was the main genus related to denitrification and drug degradation. Enzymes involved in ω/β-oxidation were inferred, such as ibuprofenoyl-CoA epimerase.